The early life of a leaf‐cutter ant colony constrains symbiont vertical transmission and favors horizontal transmission. Issue 17 (5th August 2021) - Phillips, Zachary I.; Reding, Luke; Farrior, Caroline E.
Abstract: Colonial organisms host a large diversity of symbionts (collectively, parasites, mutualists, and commensals) that use vertical transmission (from parent colony to offspring colony) and/or horizontal transmission to disperse between host colonies. The early life of some colonies, characterized by the dispersal and establishment of solitary individuals, may constrain vertical transmission and favor horizontal transmission between large established colonies. We explore this possibility with the miniature cockroach Attaphila fungicola, a symbiont of leaf‐cutter ants and the mutualist fungal gardens they cultivate. The early life of a leaf‐cutter colony is characterized by the dispersal of a female alate (winged "queen") carrying a fungal pellet, and the subsequent establishment of a foundress (workerless "queen") raising her incipient fungal garden and colony. Roaches hitchhike on female alates during leaf‐cutter nuptial flights, which strongly suggests that roaches are vertically transmitted to foundresses and their incipient colonies; however, weak compatibility between roaches and incipient gardens may constrain roach vertical transmission. Reciprocally, opportunities for horizontal transmission between large established colonies with abundant fungal gardens may weaken selection against roach‐induced harm (virulence) of incipient gardens. We use a laboratory experiment, behavioral observations, field surveys, and a transmission model to estimate the effect roaches have on the survivorship of incipient gardens and the frequency of roach vertical transmission. Contrary to traditional assumptions, our results indicate that roaches harm incipient gardens and predominantly use horizontal transmission between established leaf‐cutter colonies. Ultimately, "costs of generalism" associated with infecting disparate stages of a host's lifecycle (e.g., incipient vs. established colonies) may constrain the vertical transmission of roaches and a broad range of symbionts. Abstract : It may be costly for symbionts to infect the "newborn" solitary stages of colonial hosts, constraining vertical transmission and favoring horizontal transmission between larger established host colonies. We explore this possibility using a miniature symbiotic cockroach of leaf‐cutter ants and their fungal gardens. Our study demonstrates that accounting for host colony lifecycle heterogeneity is important for understanding symbiont transmission dynamics and evolution.